Hotels’ online reputation management: benefits perceived by managers. - Pérez-Aranda, Javier Ramón; Vallespín-Arán, María Luisa; Molinillo-Jiménez, Sebastián (My University, 2019)
Purpose – This study aims to develop a measurement model to help hotels manage their reputation within the context of online reviews and ratings platforms and evaluate the impact of this reputation management on the benefits derived by the hotels, as perceived by their managers. Design/methodology/approach – Partial least squares was used to assess the model and make a causal predictive analysis, using data from a survey of a random sample of 335 Spanish hotel managers and personnel involved in reputation management. Findings – This study shows the operationalization of hotel reputation management as a superordinate second-order construct affecting six individual first-order dimensions, strongly impacting on three key benefits as perceived by hotel managers (i.e. financial benefits, customer relationship benefits and customerbased brand benefits), within the context of online review platforms. Practical implications – Based on the results of this study, hotel managers can improve the effectiveness of their management of ratings and reviews. They can also learn which aspects they should focus on when managing ratings and reviews. Originality/value – Based on the opinions of hotel managers, a causal model for managing online reviews was developed and validated. This study shows how reputation management affects the benefits derived by hotels as perceived by their managers.
Keywords: Hoteles y pensiones - Reseñas; Consumidores; Online review; User-generated content; Reputation management; Perceived hotel benefits